Peningkatan Hasil Belajar Siswa Melalui Model Problem Based Learning Pada Mata Pelajaran PPKn Kelas III SD Negeri Guyung 4 - Dewi Ratih Mitra; Wasilatul Murtafiah; Yunianto Taufik Hidayat Eko; Iswati Nuning (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2023)
This reseach to determine the increase in learning outcomes in Pancasila and civic education subjects using the Problem Based Learning learning model. This research is one of the solutions to improve student learning outcomes through the Problem Based Learning (PBL) learning model, which is a learning model that involves the activeness of students to always think critically and skillfully in solving a problem. The method used in this research is classroom action research (PTK) which is a research model that includes four components or stages: planning, action, observation, and reflection. The subjects in this study were third grade students of SDN Guyung 4 in the even semester of the 2022/2023 academic year. The subjects in this study amounted to 11 students consisting of 9 boys and 2 girls. The instruments (data collection tools) used are questions, interviews, documentation and observation sheets. Based on the results of the research that has been carried out, it shows an increase in student evaluation results, which initially averaged 62,72 in the pre-cycle, increased in cycle I, students had an average of 66,36 while in cycle II they had an average of 80 with a percentage increase from pre-cycle to cycle I of 3,64% and cycle I to cycle II increased by 13,64% and from pre-cycle to cycle II increased by 17,28%. Thus, it can be concluded that the Problem Based Learning (PBL) learning model can improve student learning outcomes in Pancasila and citizenship education subjects in the material of the Pancasila principles in class III SDN Guyung 4, Gerih District, Ngawi Regency.